MARCHING PRING WHITE LION DI DESA KALIMANGGIS KECAMATAN SUBAH KABUPATEN BATANG (Kajian : Bentuk Aransemen dan Eksistensinya) (Jurnal Seni Musik, 2015)
Purpose in this research is: (1) knowing and descripting shape music instrumen of Marching Pring White Lion in Kalimanggis village Subah sub-district Batang district. (2) knowing and descripting existence of Marching Pring White Lion in Kalimanggis village Subah sub-district Batang district. Approach use in this research is descriptive and qualitative approach. Strategy data collection in use observed technique, interview, and documentation. Data analysis technique in use is cover in three principal component, data reduction, data dish, and verification. In this reaserch find music arransement divided for two is ritmic music arransement and mix music arransement. Ritmic music arransement is playing music instrument non melodic, function as fill in, instrument in use tongprek, snare drum, bass drum, cymbal, tamborin, and triol. Mix music arransement is music arransement for instrument melodis and non melodic. Existence Marching Pring White Lion in Kalimanggis village Subah sub-district Batang district since the beginning from1976 until now 2015 is very famous in surrounding area and outside the territory, until now the group do training in week end, and in addition to certain events of this art is still doing performances in various regions.